Medical devices surgical and image-guided technologies - Culjat, Martin, 1977-; Singh, Rahul, 1975-; Lee, Hua, 1952- (Wiley, 2013)
Biomedical Devices and Technology is a textbook for an introductory seminar course on biomedical devices and technology. The book covers devices and systems in diagnostic, surgical, and implant procedures, prepared by the much-respected faculty members at the UCLA School of Medicine.